Outcomes of patients with up to 6 years of follow-up from a phase 2 study of idelalisib for relapsed indolent lymphomas. Issue 5 (16th April 2021) - Wagner-Johnston, Nina D.; Schuster, Stephen J.; deVos, Sven; Salles, Gilles; Jurczak, Wojciech J.; Flowers, Christopher R.; Viardot, Andreas; Flinn, Ian W.; Martin, Peter; Xing, Guan; Rajakumaraswamy, Nishanthan; Gopal, Ajay K.
Abstract: The phase 2 study of idelalisib monotherapy for indolent non-Hodgkin lymphomas (iNHLs) was completed in 2018; final efficacy and safety data with up to 6.7 years long-term follow-up are reported. Patients with iNHL refractory to both rituximab and an alkylating agent were enrolled and received 150 mg idelalisib twice daily ( N  = 125). Idelalisib resulted in an overall response rate of 57.6% with 34.4% continuing therapy for ≥12 months. The median progression-free survival and duration of response were 11.0 and 11.8 months for follicular lymphoma, 22.2 and 20.4 months for lymphoplasmacytic lymphoma/Waldenström's macroglobulinemia (LPL/WM), and 6.6 and 18.4 months for marginal zone lymphoma (MZL). Median overall survival after extended follow-up was 48.6 (95% CI 33.9, 71.7) months. Long-term follow-up did not reveal new safety concerns. These data indicate beneficial outcomes with longer follow-up after idelalisib for treatment of iNHL including in patients with LPL/WM and MZL.